Answer: (19,520-1,478) x 8
Write the word sentence as an inequality.
The quotient of a number g and -2 is fewer than -6.
An inequality is a
Answer:
[tex]\displaystyle -6 > \frac{g}{-2}[/tex]
Step-by-step explanation:
[tex]\displaystyle \frac{g}{-2} < -6[/tex]
The keywords are fewer than, so the inequality receives the less than symbol, NOT greater than or equal to.
** The above answer is written in reverse, which is the exact same result.
I am joyous to assist you anytime.
The word sentence translates to the inequality 'g / -2 < -6', representing the relationship where the quotient of a number g and -2 is less than -6.
Writing the word sentence 'The quotient of a number g and -2 is fewer than -6' as an inequality involves translating the words into a mathematical expression. Inequality symbols are used to show how two measurements, or in this case, expressions, are related. The quotient of a number and another number is represented by the division of those two numbers. 'Fewer than' indicates that the expression on the left side is less than (<) the expression or value on the right side.
Therefore, the statement can be translated to the mathematical inequality as g / -2 < -6. This inequality shows the relationship between the variable g and the numbers -2 and -6, with the quotient of g and -2 being less than -6.
Which equation shows y=-x+4 is in standard form?
2x - y=8
Ox+2y=-8
O
x + 2y = 8
2x + y = 8
Answer:
(c) [tex]x + 2y = 8[/tex]
Step-by-step explanation:
The question is missing some important data which is necessary to solve it.
The correct question is as follows:
Which equation shows [tex]y=-\frac{1}{2}x+4[/tex] is in standard form?
(a) [tex]2x-y=8[/tex]
(b) [tex]x + 2y=-8[/tex]
(c) [tex]x + 2y = 8[/tex]
(d) [tex]2x + y = 8[/tex]
Solution:
Given equation:
[tex]y=-\frac{1}{2}x+4[/tex]
To convert the given equation to standard form.
The standard form of a linear equation is given by:
[tex]Ax+By=c[/tex]
where
A is a positive integer and B and C are integers
We have:
[tex]y=-\frac{1}{2}x+4[/tex]
Multiply both sides by 2 to remove the fraction
[tex]2y=(-\frac{1}{2}x\times 2)+(4\times 2)[/tex]
[tex]2y=-x+8[/tex]
Adding [tex]x[/tex] both sides
[tex]x+2y=x-x+8[/tex]
[tex]x+2y=8[/tex]
∴ The standard form of the equation is ⇒ [tex]x+2y=8[/tex]
Select the correct answer.
The formula for finding the kinetic energy, E, of an object is given below, where m represents the mass and v represents the speed of
the object.
E = mv2
Solve the formula for v.
You can solve the kinetic energy formula E = mv² for 'v' by first dividing by 'm' to get E/m = v² and then taking the square root of both sides, resulting in v = sqrt(E/m).
Explanation:The kinetic energy of an object is given by the equation E = mv², where 'm' is the mass of the object and 'v' is its speed. If you want to solve this formula for 'v', you would start by dividing both sides of the equation by 'm'. Doing this, you would get: E/m = v². Then, you would take the square root of both sides to isolate 'v'. This would give you: v = sqrt(E/m), where sqrt stands for 'square root'.
This means that the speed of the object can be found by taking the square root of the kinetic energy divided by the mass of the object.
Learn more about Kinetic Energy here:https://brainly.com/question/26472013
#SPJ12
The expression for y is y = [tex]\frac{2E}{m}[/tex].
To solve the kinetic energy formula E=[tex]\frac{1}{2}[/tex] [tex]mv^{2}[/tex] for y, we need to isolate y on one side of the equation. The formula can be rearranged as follows:
E=[tex]\frac{1}{2}[/tex][tex]mv^{2}[/tex]
Multiply both sides of the equation by 2 to eliminate the fraction:
2 E = [tex]mv^{2}[/tex]
Now, to solve for y, which is represented by [tex]mv^{2}[/tex] , divide both sides by m:
y = [tex]\frac{2E}{m}[/tex]
So, the expression for y is y = [tex]\frac{2E}{m}[/tex] .
This final equation tells us that y (representing [tex]mv^{2}[/tex] ) is equal to twice the kinetic energy (E) divided by the mass (m) of the object.
In physics, [tex]mv^{2}[/tex] is often associated with momentum or the force needed to change the object's velocity.
This derived formula provides a clear representation of the relationship between kinetic energy, mass, and velocity in terms of y.
Question
The formula for finding the kinetic energy, E, of an object is given below, where m represents the mass and v represents the speed of the object. E= 1/2 mv^2 Solve the formula for y.
a male lion eats about 108 pounds of meat in a week about how much does it eat in a day
Answer:
15.43 pounds of meat in a day
Step-by-step explanation:
108 pounds per week,
1 week=7 days,
108/7=15.43
Answer:
15 remainder 3
Step-by-step explanation:
108÷7
7 because 1 week= 7 days
108÷7=
15 remainder 3
3 1⁄2 kilometers = hectometers
Answer:
35 hectometers
Step-by-step explanation:
1 kilometer=10 hectometers
3 1/2=7/2
7/2*10=35
Answer:
[tex]\large\boxed{3\dfrac{1}{2}\ kilometers=35\ hectometers}[/tex]
Step-by-step explanation:
[tex]PREFIXES\\\\mega\ (M)=10^6\\\\kilo\ (k)=10^3\\\\hecto\ (h)=10^2\\\\deko\ (da)=10\\\\decy\ (d)=10^{-1}=0.01\\\\centi\ (c)=10^{-2}=0.01\\\\mili\ (m)=10^{-3}=0.001\\\\mikro\ (\mu)=10^{-6}=0.000001[/tex]
[tex]3\dfrac{1}{2}=3.5\\\\1\ kilometers=10\ hectometers\ (1\ km=10\ hm)\\\\3\dfrac{1}{2}\ km=3.5\ km=3.5\cdot10\ hm=35\ hm[/tex]
Which equation is equivalent to 3=87/h?
Answer:
h=87/3
Step-by-step explanation:
3=87/h
h=87/3
Jerry has 9 keys on his keyring. 4 of them are silver and 5 are gold. If he randomly chooses a key.
what is the probability that the key would be silver?
Answer:
Silver keys = 4
Gold keys = 5
Total number of keys = 9
probability of getting a silver key = P(4/9)
Step-by-step explanation:
P(4/9) because 4 keys are silver among 9 keys. Probability is the number of chosen matter divided by the total number of matters.
Jack and Julio each improved their yards by planting daylilies and geraniums. They bought their supplies from the same store.
Jack spent $22 on 1 daylily and 5 geraniums. Julio spent $30 on 13 daylilies and 1 geranium. Find the cost of one daylily.
Cost of one daylily is $2 and cost of one geranium is $4.
Step-by-step explanation:
Let,
Cost of one daylily = x
Cost of one geranium = y
According to given statement;
x+5y=22 Eqn 1
13x+y=30 Eqn 2
From Eqn 1;
x=22 - 5y
Putting this value of x in Eqn 2;
[tex]13(22-5y)+y=30\\286-65y+y=30\\-64y=30-286\\-64y=-256[/tex]
Dividing both sides by -64
[tex]\frac{-64y}{-64}=\frac{-256}{-64}\\y=4[/tex]
Putting y=4 in Eqn 1
[tex]x+5(4)=22\\x+20=22\\x=22-20\\x=2[/tex]
Cost of one daylily is $2 and cost of one geranium is $4.
Keywords: linear equation, substitution method
Learn more about substitution method at:
brainly.com/question/605571brainly.com/question/5873564#LearnwithBrainly
What is 53 divided by 30?
Answer:
1.76666666666666666
Answer:
53/30=1.7666666...
Step-by-step explanation:
y-1=-2(x+3) in standard form
Answer:
2x + y + 5 = 0
Step-by-step explanation:
y − 1 = -2 (x + 3)
y − 1 = -2x − 6
2x + y + 5 = 0
What triangle congruence postulate would prove that the two triangles are congruent?
Answer:
SAS
Step-by-step explanation:
PLEASE HELP ASAP!!!
What is the approximate area of sector TSV?
Round the answer to the nearest tenth.
A. 3.1 m^2
B. 2.3 m^2
C. 1.1 m^2
D. 0.5 m^2
Answer:
C) The area of the sector TSV = 1.1 sq m.
Step-by-step explanation:
Here, the angle subtended by TSV at the center of the circle = 3 radians.
1 Radians = 57.2958°
So, 3 radians = 3 x 57.2958 = 171.887 °
⇒The angle of the sector TSV = 171.887 °
Now, the angle of any sector of a circle with angle Ф at the center
= [tex]\frac{\theta}{360} \times \pi \times (r^2)[/tex]
Here, r = 0.87 m
So, the area of the sector TSV = [tex]\frac{171.887}{360} \times \frac{22}{7} \times (0.87)^2 = 1.1358[/tex]
or, the area of the sector TSV = 1.13 sq m.
Now, rounding off the area to the nearest tenth ,we get:
The area of the sector TSV = 1.1 sq m.
A Job hotline service charges $25 plus a 4% commission c on the first month of earning if it finds work for a client. Write an equation that represents the total cost T to find a job through the hotline. What is the cost of a client earns $1500 the first month
Answer: Equation for total cost: T = $25 + 0.04E
Cost of a client who earns $1500 = $85
Step-by-step explanation:
Let E = earning in the first month
Commission (c) = 0.04 (4%) × E
Total cost will be the addition of $25 fixed amount and commission
Therefore, an equation that will represent total cost of finding a job through the hotline will be:
T = $25 + 0.04E
The cost of a client whose first month earnings is $1500 will be
T = $25 + 0.04 ($1500)
T = $25 + $60 = $85
I found that helpful
the price of a gallon of heating oil rose from 1.60 a gallon to 1.92 . by what percent did the price increase?
Answer:
20%
Step-by-step explanation:
1.92 - 1.60 = 0.32
percentage increase = (0.32/1.60) * 100 =
0.2 * 100 = 20%
Answer: required percent increase in price=20%
Step-by-step explanation:
required percent increase in price=[tex]\frac{1.92-1.60}{1.60}[/tex]\times100
=[tex]\frac{0.32}{1.60}[/tex]\times100
=[tex]0.20\times100[/tex]
=20%
The function y=ex is vertically stretched by a factor of 2, reflected across the x-axis, and then shifted down 3 units, find the resulting function.
Provide your answer below:
Answer:
1/2e^x -3
Step-by-step explanation:
The resulting function after vertically stretching y = ex by a factor of 2, reflecting it across the x-axis, and shifting it down 3 units is y = -2ex - 3.
Explanation:The original function is y = ex. To find the resulting function after the described transformations (vertically stretched by a factor of 2, reflected across the x-axis, and shifted down 3 units), we perform each transformation step by step.
Vertical Stretch: Multiplying the function by 2 gives us 2ex.Reflection across the x-axis: Multiplying by -1 to reflect it gives us -2ex.Shift down by 3 units: Subtracting 3 from the function gives us -2ex - 3.Therefore, the resulting function after all transformations is y = -2ex - 3.
how much horsepower would a Challenger SRT® Hellcat Redeye Widebody need to tow the SS Delphine up the industry standard: Davis Dam Grade Climb?
Pro Tips:
Davis Dam assumed grade = 7% Air density is sea level conditions (.002377 slugs/f^t3) w(weight) of the SS Delphine + trailer + Redeye = 3,922,000 + 150,000 + 4451 Lbs Crr = coefficient of rolling resistance = .015 Assume Combined CDA is 1555 ft^2 SAE J2807 (Davis Dam Grande Climb) - min speed is 40mpg (59 ft/s) F(drag) = 1/2p x V^2 x C(d)A F(rolling resistance) = W x cos x Crr F(weight) = W x sin F(sum) = F(drag) + F(rr) + F(weight) P = F(sum)XV convert to horsepower = P(1hp/550ft lbf/sec)
Answer: I am getting a result around the 54,800 area, so I am selecting the 55,000 HP answer.
Answer:
37769 hp
Step-by-step explanation:
from the pro tips given w ( weight of the SS Delphine + trailer + Redeye) = 3922000 + 150000 + 4451 Lbs Crr = 4076451 ibf
coefficient of rolling resistance = 0.015
Combined CDA = 1555 ft ^2
to get Ф = tan ⁻¹ ( 0.07 ) = 4.0041 degrees
To get F (w) you will multiply it with sin Ф
= F ( w ) = 4076451 ibf * sin( 4.0041 ) = 284655.02 Ibf
to calculate F ( rr ) you will multiply it with cos Ф
F( rr) = 4076451 ibf * 0.015 * cos ( 4.0041 ) = 60997.50 ibf
the total sum of F ( force ) will be
F ( rr ) + F ( w)
= 60997.50 + 284655.02 = 352085.82 Ibf
therefore P ( power ) will be
p = 352085.82 ibf * 59 ft/s = 20773063.27 ft*ibf/s
to calculate how much horsepower the challenger will need to tow the SS Delphine will be calculated as below
HP = (20773063.27 ft*ibf/s ) * ( 1 hp / 550 ft*ibf/s ) = 37769.21 = 37769 hp
Peter filled 5 cups each with 1 pound of candy. How much candy did the 5 cups contain altogether? 5 1/2 pounds
6 1/2 pounds 7 pounds 7 1/2 pounds
Step-by-step explanation: i think it is B
How can ΔABC be mapped to ΔXYZ?
Triangles A B C and X Y Z are shown. The lengths of sides A B and X Y are 25 centimeters. The lengths of sides A C and X Z are 29 centimeters. Angles B A C and Y X Z are 36 degrees. Triangle A B C is slightly higher and to the left of triangle X Y Z. Triangle A B C is rotated to form triangle X Y Z.
First, translate ____________________. Next, rotate ΔABC about B to align the sides and angles.
vertex B to vertex Z
vertex B to vertex Y
vertex A to vertex Z
vertex A to vertex Y
Answer:
Vertex B to vertex Y
Step-by-step explanation:
The diagram shows two triangles ABC and XYZ. These triangles are congruent by SAS postulate, because
AB = XY = 25 cm;AC = XZ = 29 cm;∠A = ∠X = 36°.Congruent triangles have congruent corresponding sides and angles, so translation and rotation must be completed such that
vertex A coincides with vertex X;vertex B coincides with vertex Y;vertex C coincides with vertex Z.So, first, translate vertex B to vertex Y. Next, rotate ΔABC about B to align the sides and angles.
What is the image of −6,3)
(−6,3) after a reflection over the y-axis?
Final answer:
The image of the point (-6,3) after a reflection over the y-axis is (6,3), because a reflection over the y-axis changes the sign of the x-coordinate while leaving the y-coordinate unchanged.
Explanation:
The question is asking for the result of a reflection of the point (-6,3) over the y-axis. A reflection over the y-axis will invert the x-coordinate of the point but leave the y-coordinate unchanged. Hence, the reflected point will have the same y-coordinate but the opposite x-coordinate. The transformation formula for a reflection over the y-axis is (x, y) to (-x, y).
Applying this formula to the point (-6,3), we change the sign of the x-coordinate from -6 to 6, while the y-coordinate remains the same. Therefore, the image of the point (-6,3) after the reflection over the y-axis is (6,3).
Parallelograms:
ABCD∼A1B1C1D1.
Find BC, B1D1
Answer:
[tex]BC = 4.8[/tex] and [tex]B_{1}D_{1} = 6.25[/tex]
Step-by-step explanation:
The parallelograms ABCD and [tex]A_{1} B_{1} C_{1}D_{1}[/tex] are similar.
Now, AB = 8 (Given in the figure), so CD = 8.
Now, we can write, [tex]\frac{BC}{B_{1}C_{1}} = \frac{CD}{C_{1}D_{1}}[/tex]
⇒ [tex]\frac{BC}{3} = \frac{8}{5}[/tex]
{Since, given that [tex]B_{1}C_{1} = 3[/tex] and [tex]C_{1}D_{1} = 5[/tex]}
⇒ [tex]BC = \frac{8 \times 3}{5} = 4.8[/tex] (Answer)
Again, we can write, [tex]\frac{BD}{B_{1}D_{1}} = \frac{CD}{C_{1}D_{1}}[/tex]
⇒ [tex]\frac{10}{B_{1}D_{1}} = \frac{8}{5}[/tex] {Since, BD = 5 + 5 = 10}
⇒ [tex]B_{1}D_{1} = \frac{5 \times 10}{8} = 6.25[/tex] (Answer)
wuts 4x +6x= plzzzzzzzzzzzzzz help me im in 4th grade
Answer:
10x
Step-by-step explanation:
Answer:
10x
Step-by-step explanation:
since they both are the same just add them and done
2,952 = 72=
It’s is another hard question on my math homework pls help
Answer:41
Step-by-step explanation:
Match the real-world problem to its constant of proportionality.
a. $18.36 for 3 pizzas [box]
b. $4.17 for 3 pounds of bananas [box]
c. $16.48 for 4 pounds of potatoes [box]
d. 2 cups of flour to make 24 cookies [box]
Place in the box 12 4.12 6.12 1.39
WIN BRAINLIEST
Answer:
a. $18.36 for 3 pizzas : k = 6.12
b. $4.17 for 3 pounds of bananas . k = 1.39
c. $16.48 for 4 pounds of potatoes . k = 4.12
d. 2 cups of flour to make 24 cookie . k = 12
Step-by-step explanation:
PROPORTIONALITY:
Two quantities x and y are said to proportional to each other
if for x ∝ y , x = y k.
Here, k is called the PROPORTIONALITY CONSTANT.
⇒[tex]x \propto y \implies k = \frac{x}{y}[/tex]
Now, for the given quantities:
a. $18.36 for 3 pizzas [box]
Here, [tex]k = \frac{x}{y} = \frac{18.36}{3} = 6.12[/tex]
So, the proportionality constant is 6.12.
b. $4.17 for 3 pounds of bananas [box]
Here, [tex]k = \frac{x}{y} = \frac{4.17}{3} = 1.39[/tex]
So, the proportionality constant is 1.39.
c. $16.48 for 4 pounds of potatoes [box]
Here, [tex]k = \frac{x}{y} = \frac{16.48}{4} = 4.12[/tex]
So, the proportionality constant is 4.12.
d. 2 cups of flour to make 24 cookies
Here, [tex]k = \frac{x}{y} = \frac{24}{2} = 12[/tex]
So, the proportionality constant is 12.
Jo is thinking of a number. Four less than 9 times the number is 176. Find Jo’s number.
Answer:
Jo's thinking about the number 20.
Step-by-step explanation:
9x-4=176
9x=176+4
9x=180
x=180/9
x=20
how can you find the function rule from a table of values
You go to a school dance. There is an entrance fee, and there are slices of pizza for sale. After having 1 slice of pizza, you have spent a total of $6. After having 2 more slices of pizza, you have spent a total of $10. Write an equation that represents the total cost y after buying x slices of pizza at the dance
Answer:
Equation that represents the total cost is y = 4 + 2 x
Step-by-step explanation:
Here, x : slices of pizza eaten at the dance.
y : total cost paid in the school dance
Let a : Cost of each slice of pizza.
So, according to the question:
Entrance fee + cost 1 slice of pizza = $6
or, Entrance fee = $ 6 - Cost of 1 slice ....... (1)
Similarly, Entrance fee + cost 3 slice of pizza = $10
or, Entrance fee = $ 10 - Cost of 3 slice ............ (2)
Comparing both equation , we get:
$ 6 - Cost of 1 slice = $ 10 - Cost of 3 slice
or, 6 - a = 10 - 3 a
or, 2 a = 4
⇒ a= 2, So the cost of each slice of pizza = $2
Putting the value of a in 1 we get
Entrance fee = 6 - $ 2 =$4
Now, the cost of x slice of pizza = x ( $2) = 2x
So, the total cost y for x slice of pizza = Entrance fee+ Cost of x slices
or, y = $ 4 + 2 x
Equation that represents the total cost is y = 4 + 2 x
Final answer:
The equation that represents the total cost y after buying x slices of pizza is y = 2x + 4, which includes the cost of each slice of pizza ($2) and the entrance fee ($4).
Explanation:
To write an equation that represents the total cost y after buying x slices of pizza at the dance, you can use the information given to create two points: (1, $6) and (3, $10). From the first point, you know there is a fixed entrance fee plus the cost of one slice of pizza. By the time you purchase two more slices (for a total of three), the cost is $10. This scenario implies that each additional slice of pizza has a constant price.
With two points, you can find the slope of the line, which represents the price of each slice of pizza. The slope m is the change in cost divided by the change in the number of slices: m = ($10 - $6) / (3 - 1) = $4 / 2 = $2 per slice. The entrance fee is the y-intercept of the line, which is the initial cost without any pizza, and can be found by extending the line back to the y-axis. The total cost without any pizza is the cost after one slice minus the cost of that slice, which gives us $6 - $2 = $4.
The final equation becomes y = 2x + 4, where y represents the total cost and x represents the number of slices of pizza purchased.
answer the question below please answer correctly
Answer:
x=4
Step-by-step explanation:
Using cross multiplication, we can simplify the equation to
-15x=-60
Then we can divide by -15 on both sides getting x=4
Select the correct answer from the drop-down menu.
If A and B are independent events, P(A and B) =
P(a)
Explanation I just did it :)
For independent events A and B, the probability of both occurring P(A and B) is the product of their individual probabilities: C. P(A) * P(B).
What are independent events?Independent events are events in probability theory where the occurrence of one event does not affect the occurrence or likelihood of the other.
Let's use the definition of independent events to derive the formula for the probability of the intersection of two independent events.
If events A and B are independent, then the definition of independence is given by:
P(A and B) = P(A) * P(B)
This means that the probability of both events A and B occurring is the product of the individual probabilities of A and B.
So, if A and B are independent events, P(A and B) = P(A) * P(B). Therefore, the correct answer is C. P(A) * P(B).
Learn more about independent events on:
https://brainly.com/question/27665211
#SPJ3
what is the answer to 5.48 * 15.12
Answer:
82.8576
Step-by-step explanation:
I have a precalculus problem about solving the equation can somebody help me please
Answer:
Yeah
Step-by-step explanation:
find a formula